Academic Language and Didactic Potential of Writing: Review of a Chilean Study Program - Castro-Cifuentes, Mauricio Alejandro (2024)
The present study has as its central element the updating of the Curricular Bases for the area of Language and Literature in secondary education in Chile, specifically, in the context of an elective subject. Based on a qualitative methodology of descriptive scope and using the technique of content analysis, a ministerial Program of Study is examined. Two objectives are outlined, on the one hand, to determine the theoretical conceptions that underlie writing in academic language and, on the other hand, to trace the main written genres that are articulated as spaces of knowledge. The documentary analysis reports a conception of epistemic potential in academic language and an enabling function, since it allows participation in specialized communities. It is concluded that secondary education is a key moment to develop the appropriation of this register, since they constitute borderline genres between school and university education.